0033 Recurrent Circadian Disruption While Minimizing Sleep Loss in Humans Impairs Glucose Tolerance Only in The Presence of High-Fat Diet. (27th May 2020) - Zitting, K; Yuan, R K; Vujovic, N; Klerman, E B; Quan, S F; Scheer, F A; Wang, W; Buxton, O M; Williams, J S; Duffy, J F; Czeisler, C A
Abstract: Introduction: Nearly 14% of Americans experience chronic circadian disruption due to shift work, increasing their risk of obesity and cardiometabolic disorders. These disorders are also exacerbated by modern eating habits such as frequent snacking and consumption of high-fat foods. Here we used a forced desynchrony protocol to investigate the effect of 3 weeks of recurrent circadian disruption (RCD) with minimal sleep loss on glucose metabolism in humans on a lower or higher fat diet (LFD and HFD, respectively). Methods: Six healthy adults (38-69yrs; 3f) participated in a 37-day inpatient protocol with LFD (25–27% fat) and 15.67-hr fasting duration, or HFD (45–50% fat) and 13-hr fasting duration. The protocol included three weeks of RCD consisting of 28-hr "days" with 11.67-hr sleep opportunities (=10hrs/24hr). Glucose and insulin responses to a standardized breakfast were conducted at baseline, at an aligned circadian phase after 2–3 weeks of exposure to RCD, and after 1 week of recovery. Frequent blood samples were assayed for glucose and insulin; the Area-Under-Curve was calculated from start of breakfast through postprandial minute 180. Results: Total Sleep Time was similar in Baseline and RCD in both groups. Participants on the LFD showed no change in glucose AUC during RCD compared to Baseline. Insulin AUC was lower during RCD (p=0.0269) and Recovery (p=0.0443) than Baseline. In contrast, participants on the HFD showed a significant increase in glucose AUC during RCD compared to Baseline (p<0.0001); AUC returned to Baseline during Recovery. There was no significant change in insulin AUC on the HFD. Conclusion: RCD (in the absence of sleep loss) led to impaired glucose tolerance when combined with HFD, but not when combined with LFD. These results suggest that LFD may be part of healthy strategies for people experiencing RCD. Support: Study supported by P01AG009975 and conducted in the Brigham and Women's Hospital Center for Clinical Investigation, part of Harvard Clinical and Translational Science Center supported by UL1TR001102. Authors supported by a fellowship from the Finnish Cultural Foundation (KMZ); T32HL007901 and F32HL143893 (RKY); T32HL007901 and F32AG051325 (NV); K24HL105664 (EBK); R01HL118601 (FAJLS).